The occurrence of acute primary angle closure triggered, aggravated, and accelerated by COVID-19 infection: retrospective observational study - Yue Ying; Yue Ying; Yue Ying; Ruyi Zhai; Ruyi Zhai; Ruyi Zhai; Yanan Sun; Yanan Sun; Yanan Sun; Qilian Sheng; Qilian Sheng; Qilian Sheng; et al. (Frontiers Media S.A., 2023)
IntroductionThe aim of this study is to demonstrate the relevance of primary acute angle closure (APAC) and COVID-19 infection, compare the demographic features and manifestations between COVID-19 positive and negative patients with APAC, and infer the underlying mechanism.MethodsThis study is based on all patients diagnosed with APAC at the glaucoma center of Eye, Ear, Nose and Throat Hospital of Fudan University (Fenyang road center) from 15th December 2022 to 11th January 2023. Totally 171 APAC cases were categorized into COVID-19 positive and negative group. Demographic features and final treatment level of the patients were compared between the two groups. Clinical manifestations, intraocular pressure, and anterior chamber configuration were also compared between the two groups.ResultsIn the COVID-19 positive group, the number of cases with APAC onset spiked in 22nd December 2022, which coincided with the spike of COVID-19 antigen positive people. Compared to the COVID-19 negative group, COVID-19 positive APAC patients were younger with a lower percentage of APAC history. Additionally, more eyes of COVID-19 positive APAC patients showed keratic precipitates. COVID-19 positive eyes had significantly larger anterior chamber depth with a more dilated pupil. Therefore, COVID-19 infection could probably act as a triggering factor of APACDiscussionThe onset of APAC might be accelerated by COVID-19 infection for patients with younger age and milder anatomical configuration. Additionally, COVID-19 related APAC cases might have a more abrupt and fierce onset. Ophthalmic emergent services should not be neglected during the epidemic period.